Knowledge of recent medical graduates and views of stakeholders and teachers regarding medical ethics and professionalism in Bangladesh - Jahan, Sharmin; Flora , MS (Bangladesh Journal of Medical Education, 2022)
Medical education aims to produce competent medical professionals and gives emphasis on competency-based learning in Bangladesh. Medical ethics and professionalism are considered as a core competency. A competent physician can ensure patient-centered health care system. This was an effort to obtain data regarding the knowledge of recent medical graduates and the opinion of medical educational stakeholders and teachers about medical ethics and professionalism at undergraduate medical education in Bangladesh. This mixed-method study was conducted in two rounds. The Round I was conducted from January 2018 to June 2019 for assessing the knowledge of 308 recent medical graduates towards medical ethics and professionalism. In Round II, key informant interviews were conducted among 30 medical educational stakeholders and teachers from July 2020 to December 2020. Data were collected by pre-tested self administered semi-structured questionnaire and interview guidelines. The percentages of recent medical graduates who could give correct answers regarding autonomy, justice, presenting a subject to visual social media, breaching of confidentiality, organ donation and medical certificate were 19.8%, 54.9%, 73.1%, 37.3%, 91.6% and 74.4% respectively. Most of the medical educational stakeholders and teachers (80%) expressed their opinion related to curriculum. They also suggested for practicing ethics (20.0%) and training (20.0%). A gap was observed in the knowledge regarding medical ethics and professionalism of recent medical graduates. To improve practice of ethics and professionalism, enhancement of the knowledge by incorporating “medical ethics and professionalism” in curriculum might be considered. A separate compulsory module for training on medical ethics and professionalism can be added at pre-internship period for the recent medical graduates. Bangladesh Journal of Medical Education Vol.13(1) January 2022: 40-48